Parikh factor matrices for finite words of rectangular Hilbert space filling curve - Jeya Bharathi, S; Thiagarajan, K; Navaneetham, K (International Journal of Engineering and Technology, 2018)
Ordered Factor Patterns in a word over an ordered alphabet aredefined.  Also, Parikh StrictlyAscending FactorMatrix and Parikh StrictlyDescending Factor Matrix of a given word are introduced.  The relation of these matrices with Ordered Factor Patterns is discussed.  Moreover, the ParikhStrictly Ascending FactorMatrices and the Parikh Strictly Descending FactorMatricesfor finitewords of Rectangular Hilbert Space Filling Curve are determined.